The Legal Position of Registered Letters and Their Effectiveness in Realizing the Principle of Simple, Fast and Low-Cost Justice (Study at the Simalungun Religious Court) - Muhammad Husni Dalimunthe; Henry Aspan; T. Riza Zarzani (Yayasan Multidimensi Kreatif, 2025)
This paper wants to see how the legal position of Perma No. 7 of 2022 is related to the summoning of the parties to attend the trial in court. The summons according to Perma Number 7 of 2022 is carried out through a registered letter where the summons is carried out by an officer outside the court bailiff, namely PT. Pos Indonesia, while in the previous regulation, namely in HIR/RBg. the person who is obliged to make a summons is a court bailiff, and Government Regulation Number 9 of 1975 the summons is carried out by an officer ordered by the chairman of the religious court. After the legal position, it was also examined how effective the PERMA was when applied in a judicial work unit, namely the Simalungun Religious Court. The method used in this study is normative-empirical juridical (applied law research) where for normative law it examines legal norms, rules and principles contained in laws and regulations, and finds out the facts in the field from the application of rules in a work unit, namely the Simalungun Religious Court. From the results of the research, the researcher obtained the results that although there is no legal void in the law that regulates the summons of litigants to attend the trial, the legal position of Perma Number 7 of 2022 remains strong because the rules governing the summons are not rigid and provide space to make a perma that regulates summonses through registered letters. For the effectiveness of its implementation, Perma number 7 of 2022 is very effective for the principle of simplicity and low cost but not effective enough for the principle of fast justice. This means that the issuance of Perma Number 7 of 2022 does not deviate from higher rules and its application is very effective for the realization of the principles of the judicial trilogy, especially in terms of simple and cost-effective principles.